Study And Analysis Of Piezo Bender For Energy Harvesting Application Using Matlab Simulink - Kamar Shah, Noor Fajwa (Universiti Sains Malaysia, 2022)
Piezoelectric energy harvesting (PEH) is a device used to convert vibration energy or mechanical energy from the environment into electrical energy. PEH can be presented in a few configurations or structures such as cantilever beam, cymbal, and stack type. In this paper, the primary focus is to study and analysis PEH of bimorph cantilever beam using MATLAB Simulink. A piezoelectric bimorph cantilever beam configuration can be represented by a "Piezo bender" block model found in the Simulink and MATLAB software packages. The electromechanical effect like output power and voltage generated by a piezo bender with two separate vibration sources are analysed and simulated within this particular research piece's scope. The vibrating source of one variant has a constant frequency, while the source of the second variant has an increasing frequency. The energy obtained from the vibration system is collected by a piezo bender, which then transforms it into electrical energy. The collected energy is used to power a continuous load and charge a storage battery. The findings indicate that the output power of the piezo bender when utilising a constant frequency is more excellent, coming in at 67.0288 mW, compared to the output power when increasing the frequency, which is just 0.67493 mW. This is because a vibration source with a constant frequency is far closer to the resonant frequency compared to non-constant frequency. From these findings simulation results and studies, it might be used as a reference to develop a PEH devices into reality.